Gene Editing Regulation and Innovation Economics - Whelan, Agustina I.; Gutti, Patricia; Lema, Martin A. (Frontiers in Bioengineering and Biotechnology, 2020)
Argentina was the first country that enacted regulatory criteria to assess if organisms resulting from New Breeding Techniques (NBTs) are to be regarded as Genetically Modified Organisms (GMOs) or not. The country has now accumulated four years of experience applying such criteria, reaching a considerable number of cases, composed mostly of gene-edited plants, animals and microorganisms of agricultural use. This article explores the effects on economic innovation of such regulatory experience. This is done by comparing the cases of products derived from gene editing and other NBTs that have been presented to the regulatory system, against the cases of GMOs that have been deregulated in the country. Albeit preliminary, this analysis suggests that products from gene editing will have different profiles and market release rates compared with the first wave of products from the so called “modern biotechnology”. Gene editing products seems to follow a much faster development rate from bench to market. Such development is driven by a more diverse group of developers, and led mostly by small and medium enterprises (SMEs) and public research institutions. In addition, product profiles are also more diversified in terms of traits and organisms. The inferences of these findings for the agricultural and biotechnology sectors, particularly in developing countries, are discussed.